Assessing priorities for allocation of donor liver grafts: survey of public and clinicians. Issue 7152 (18th July 1998) - Neuberger, James; Adams, David; MacMaster, Paul; Maidment, Anita; Speed, Mark
Abstract: Objectives : To compare the priorities of the general public, family doctors, and gastroenterologists in allocating donor livers to potential recipients of liver allograft. Design Representative quota sampling of 1000 members of the general public and 200 family doctors, and a postal questionnaire of 100 gastroenterologists. Subjects : Respondents were given eight hypothetical case histories (based on real patients) and asked to select recipients for four donor livers. Cases were selected to identify controversial areas such as extremes of age, misuse of alcohol, and intravenous drugs. Respondents were also asked to select the least deserving case and which of seven possible factors (time on waiting list, outcome, age, value to society, return to work, previous use of illicit drugs, and involvement of alcohol in the liver damage) should be used to select patients already listed for transplantation. Focus groups were also held to explore further the reasons for the choices given. Results : There were considerable differences between the three groups in the choice of the recipients, although alcohol use and antisocial behaviour always rated low. For selection of recipients the general public thought that, in decreasing order of importance, age, outcome, and time on the waiting list were the most important factors in selecting recipients; family doctors rated outcome, age, and likely work status after transplantation and the gastroenterologists outcome, work status, and non-involvement of alcohol in the cause of the liver disease as the most important factors. Conclusions : The views of the public are at variance with those of clinicians. Further debate is required to ensure an equitable and appropriate distribution of a scarce resource.